Identifikasi Telur Cacing Nematoda Usus Pada Feses Pemulung Anak-Anak di Tempat Pembuangan Akhir (TPA) Tamangapa Antang, Kota Makassar - Mutiara, Friscila; Hartati; Thaslifah (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
Helminthiasis is an infectious disease caused by parasitic worms from the intestinal nematode group, which includes Soil-Transmitted Helminths (Ascaris lumbricoides, Trichuris trichiura, Hookworm, Strongyloides stercoralis) and Non-Soil-Transmitted Helminths (Enterobius vermicularis, Trichinella spiralis). This infection is common among elementary school-aged children, especially those frequently in contact with soil, such as child scavengers. The objective of this study was to identify intestinal nematode species in the feces of child scavengers at the Tamangapa Antang landfill. Conducted at Megarezky University, the study analyzed 24 fecal samples collected from child scavengers. The samples were examined using the flotation method, and nematode egg morphology was identified under a microscope at magnifications of 40x to 100x. The findings showed that 17 samples (71%) were positive for nematode eggs, while 7 samples (29%) were negative.